Association Between Prescribed Ibuprofen and Severe COVID‐19 Infection: A Nationwide Register‐Based Cohort Study. Issue 6 (21st October 2020) - Kragholm, Kristian; Gerds, Thomas A.; Fosbøl, Emil; Andersen, Mikkel Porsborg; Phelps, Matthew; Butt, Jawad H.; Østergaard, Lauge; Bang, Casper N.; Pallisgaard, Jannik; Gislason, Gunnar; Schou, Morten; Køber, Lars; et al.
Abstract : Recommendations regarding ibuprofen use in relation to coronavirus disease 2019 (COVID‐19) have been conflicting. We examined the risk of severe COVID‐19 between ibuprofen‐prescribed and non‐ibuprofen patients with COVID‐19 in a nationwide register‐based study of patients with COVID‐19 in Denmark between the end of February 2020 and May 16, 2020. Patients with heart failure ( n  = 208), < 30 years ( n  = 575), and prescribed other nonsteroidal anti‐inflammatory drugs ( n  = 57) were excluded. Patients with ibuprofen prescription claims between January 1, 2020, and before COVID‐19 diagnosis or April 30, 2020 (last available prescription) were compared with patients without ibuprofen prescription claims. Outcome was a 30‐day composite of severe COVID‐19 diagnosis with acute respiratory syndrome, intensive care unit admission, or death. Absolute risks and average risk ratios comparing outcome for ibuprofen vs. non‐ibuprofen patients standardized to the age, sex, and comorbidity distribution of all patients were derived from multivariable Cox regression. Among 4, 002 patients, 264 (6.6%) had ibuprofen prescription claims before COVID‐19. Age, sex, and comorbidities were comparable between the two study groups. Standardized absolute risks of the composite outcome for ibuprofen‐prescribed vs. non‐ibuprofen patients were 16.3% (95% confidence interval (CI) 12.1–20.6) vs. 17.0% (95% CI 16.0–18.1), P  = 0.74. The standardized average risk ratio for ibuprofen‐prescribed vs. non‐ibuprofen patients was 0.96 (95% CI 0.72–1.23). Standardized absolute risks of the composite outcome for patients with ibuprofen prescription claims > 14 days before COVID‐19 vs. ≤ 14 days of COVID‐19 were 17.1% (95% CI 12.3–22.0) vs. 14.3% (95% CI 7.1–23.1). In conclusion, in this nationwide study, there was no significant association between ibuprofen prescription claims and severe COVID‐19.